2017
DOI: 10.1099/ijsem.0.002355
|View full text |Cite
|
Sign up to set email alerts
|

Sediminibacterium roseum sp. nov., isolated from sewage sediment

Abstract: A novel bacterial strain, designated SYL130, was isolated from the sewage sediment of a park in Busan, Korea. The strain was aerobic, producing orange colonies on R2A agar. Cells were single, Gram-stain-negative rods and were motile by gliding. Phylogenetic analyses, based on 16S rRNA gene sequences, showed that strain SYL130 was most closely related to Sediminibacterium aquarii JCM 31013 (96.1 %). The major fatty acids (>5 % of the total) of strain SYL130 were iso-C15 : 0 (28.3 %), iso-C15 : 1 G (23.2 %), iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We performed LEfSe analysis to compare this differential abundance across months, categorised by low or high COVID-19 incidence. A histogram of the LDA scores (Fig 3a) indicates that the low case period was characterised by the prevalence of mostly uncultured genera along with common gut microbiota members like Erysipelotrichaceae (Shanks et al 2013), Sedinibacterium which is commonly found in sewage sediments (Song et al 2017) and Methanosarcinales found in landfill heaps and even animal gut (Volmer et al 2023) Other ARGs, such as sul1 and mcr-1, also increased during this period. Mobile genetic element -int1 was present and increased during the high case period.…”
Section: Resultsmentioning
confidence: 99%
“…We performed LEfSe analysis to compare this differential abundance across months, categorised by low or high COVID-19 incidence. A histogram of the LDA scores (Fig 3a) indicates that the low case period was characterised by the prevalence of mostly uncultured genera along with common gut microbiota members like Erysipelotrichaceae (Shanks et al 2013), Sedinibacterium which is commonly found in sewage sediments (Song et al 2017) and Methanosarcinales found in landfill heaps and even animal gut (Volmer et al 2023) Other ARGs, such as sul1 and mcr-1, also increased during this period. Mobile genetic element -int1 was present and increased during the high case period.…”
Section: Resultsmentioning
confidence: 99%
“…While complete pathways for glycolysis, the citric acid cycle, pentose phosphate shunt, beta-oxidation, and the electron transport chain are present, there is no support for the Entner–Douroroff pathway, or the metabolism of formate, methane, or sulfate reduction. In addition, unlike many of the other sediminibacterial species where menaquinone-7 is the major electron carrier ( Kim et al 2013 ; Kang et al 2014 ; Song et al 2017 ), genes encoding key enzymes for the biosynthesis of both menaquinones ( mqnA , mqnB , mqnC , mqnD , mqnE , mqnX , menI , ubiE ) and ubiquinones ( ubiA , ubiD , ubiE , ubiG , ubiH , ubiX ) are present in this strain, indicating that both may be functional. When GapMind ( Price et al 2020 ) was used to curate amino acid biosynthetic pathways, enzymes for the synthesis of nearly all 20 amino acids were identified with high confidence.…”
Section: Resultsmentioning
confidence: 99%
“…These gram-negative bacteria that are most closely related phylogenetically to Terrimonas and Niabella ( Qu and Yuan 2008 ) are actively mobile by gliding and can be strict or facultative anaerobes, or obligate aerobes ( Kim et al 2013 ). Currently, 8 species of Sediminibacterium have been isolated from sediments derived from freshwater reservoirs, sewage, activate sludge, soil from ginseng fields, and fishbowls ( Ayarza et al 2014 ; Kang et al 2014 ; Kim et al 2013 , 2016 ; Song et al 2017 ; García-López et al 2019 ; Wu et al 2021 ). During the study of 2 freshwater cyanobacteria (blue-green algae), the genome of a Sediminibacterium resident in the phycosphere of the blue-green algae was sequenced.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ralstonia showed a higher abundance in the 2 nd instar of S. frugiperda fed on maize plants in the laboratory ( Lü et al, 2023 ). The genus Sediminibacterium belongs to the phylum Bacteroidetes and mainly exists in the diverse natural environment, such as sediment, groundwater and soil ( Song et al, 2017 ), but it has been not reported in Lepidoptera. Moreover, the genus Weissella was found to be the main dominant in the 5th instar larvae, which were all purchased from Keyun Biocontrol Engineering Co., Ltd., (Jiyuan, China) and fed on artificial diet in the laboratory for several generations ( Chen et al, 2021 ; Ye et al, 2021 ), but this was not detected in our study.…”
Section: Discussionmentioning
confidence: 99%